The Reflection of Chinese as the Other in D.H. Hwang’s Chinglish: a Study of Orientalism (PANOPTICON: Journal of English Studies, 2025)
This study aimed to reflect the issue of Othering the Chinese and dominating the East in selected playscript. In this study, the writer focused on finding how the American and British characters consider the Chinese as the Other. It also analysed how and in what term the East is being dominated by the West. The object of this study is Chinglish by David Hwang (2012). Chinglish tells about an American business man, Daniel Cavanaugh goes to China in the hope for signing a contract for his family’s sign-making business with the help from his British consultant, Peter. Two of them started trying to make a relationship with Minister Cai. Finally, Daniel’s company is chosen to make the translation for the Cultural Center in Guanxi, China. As a guidance, the writer uses Orientalism theory by Edward Said (1978). This study applied qualitative research method. Based on the analysis, the American and British characters labelled the Chinese as the Other in term of identity, culture, language, education, and legal system. As they mention that Chinese are uneducated, dirty, immoral, uncivilized, and criminal. Moreover, it is also seen that the West dominate the East in terms of economic, fashion, language and culture.